Employability of College Graduates: A Literature Review - Hongyun Liao (Journal of World Economy, 2023)
The purpose of this study is to review academic research on the employability of university graduates. The paper outlines the main research topics on the employability of university graduates and outlines the gaps in previous research. This paper reviews and analyzes the themes of empirical research published in the past five years, and summarizes a total of 7 themes. These 7 themes are divided as follows. Topic 1: Development and influencing factors of graduates’ employability. Topic 2: The relationship between higher education and graduates’ employability. Topic 3: The impact of university-industry cooperation on graduates’ employability. Topic 4: The impact of social capital and professional networks on employability. Topic 5: The Importance of Improving Soft Skills and Core Employability Soft Skills. Topic 6: The impact of social mobility factors on employability. Topic 7: Globalization, social and workplace diversity require graduates’ employability.